Hitchhiker's Guide to the Galaxy : The Restaurant at the End of the Universe - Book 2 (Graphic Novel) - Adams, Douglas 1952-2001. (New York : Del Rey/Ballantine Books, 2005)
Join the cosmically displaced Arthur Dent and his uncommon comrades in arms, in their desperate search for a place to eat as they hurtle across space.
Keywords: Prefect, Ford -- Fiction; Dent, Arthur -- (Fictitious character); Fiction; Interplanetary voyages -- Fiction; Science fiction; Science fiction